Musical development of children with Autism Spectrum Disorder in Music Therapy: literature review and case report (Orfeu, 2018)
Autism Spectrum Disorder (ASD) is a disorder that affects development from an early age. Music and brain studies highlight the importance of music for human development and emphasize the role of music for people with ASD. Given the important relations between music and development, and with ASD, Music Therapy has become a therapy of increasingly potential for people with this diagnosis, as a way to improve communication and socialization. This paper aims to understand children with ASD cognitive-musical development through a literature review on the musical development of people with ASD in Music Therapy interventions, and through a case report of a child with ASD in Music-Centered Improvisational Music Therapy sessions. The results point to the need for further studies on the subject and the importance of musical development in the therapeutic treatment of children with Autism Spectrum Disorder.
Keywords: Autism; Autism Spectrum Disorder; Musical Development; Improvisational Music Centered Music Therapy